Expression of claudin, paxillin and FRA-1 in non-nodular breast lesions in association with microcalcifications: - Kandelman, José David (2013)
CONTEXT AND OBJECTIVE: The possible role of adhesion molecules in early breast carcinogenesis has been shown in the literature. We aimed to analyze early adhesion imbalances in non-nodular breast lesions and their association with precursor lesions, in order to ascertain whether these alterations exist and contribute towards early carcinogenesis. DESIGN AND SETTING: Retrospective cross-sectional study based on medical records at a private radiological clinic in São Paulo, Brazil. METHODS: We retrospectively reviewed the medical records of all consecutive women attended between August 2006 and July 2007 who presented mammographic evidence of breast microcalcifications classified as Breast Imaging Reporting and Data System Atlas (BI-RADS) type 4. These women underwent stereotaxic biopsy. Clinical, radiological and pathological data were collected, and immunohistochemical assays searched for claudin, paxillin, FRA-1 and HER-2. RESULTS: Over this period, 127 patients were evaluated. Previous BI-RADS diagnoses showed that 69 cases were in category 4A, 47 in 4B and 11 in 4C. Morphological assessment showed benign entities in 86.5%. Most of the benign lesions showed preserved claudin expression, associated with paxillin (P < 0.001). Paxillin and HER-2 expressions were correlated. FRA-1 expression was also strongly associated with HER-2 expression (P < 0.001). CONCLUSIONS: Although already present in smaller amounts, imbalance of adhesion molecules is not necessarily prevalent in non-nodular breast lesions. Since FRA-1 expression reached statistically significant correlations with radiological and morphological diagnoses and HER-2 status, it may have a predictive role in this setting.